2021
DOI: 10.1177/00220345211014799
|View full text |Cite
|
Sign up to set email alerts
|

Dentin Cross-linking Effect of Carbodiimide After 5 Years

Abstract: Carbodiimide (EDC)–based dentin primers preserve hybrid layer (HL) integrity. However, aging >1 y has not been investigated. The present study examined whether the cross-linking effect of EDC was reflected in dentin bond strength, endogenous enzymatic activity, and the chemical profile of the HL after 5-y aging in artificial saliva. Noncarious human third molars ( N = 42) were cut to expose middle/deep coronal dentin and treated as follows: group 1, dentin etched with 35% H3PO4, pretreated with a 0.3M aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
2
20
0
1
Order By: Relevance
“…Further, another study evidenced that the BS of an EGCG-modified adhesive system did not diminish within six months of water storage, while a dentin pretreatment with EGCG combined with a water solution or ethanol solution may enhance the bonding performance [ 87 ]. It was recently demonstrated that the EDC crosslinking effect stayed within the hybrid layer for 5 years in terms of the BS, collagen structure maintenance, and dentinal enzyme inhibition [ 161 ]. The researchers have recognized the impact of EGCG on improving the bonding stability to the matrix-bound MMPs’ inhibition effect [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, another study evidenced that the BS of an EGCG-modified adhesive system did not diminish within six months of water storage, while a dentin pretreatment with EGCG combined with a water solution or ethanol solution may enhance the bonding performance [ 87 ]. It was recently demonstrated that the EDC crosslinking effect stayed within the hybrid layer for 5 years in terms of the BS, collagen structure maintenance, and dentinal enzyme inhibition [ 161 ]. The researchers have recognized the impact of EGCG on improving the bonding stability to the matrix-bound MMPs’ inhibition effect [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MMPs inactivation could be irreversible and, hence, permanent. The longest in vitro aging reported so far demonstrated the cross-linking effect after 5 years of in vitro aging [36]. Notwithstanding, it must be highlighted that cross-linkers do not behave as a group, as the enzymatic inactivation has been described to be cross-linker and timedependent [30].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to alter matrix protein cross-linking and organization is fundamental to several current dental/medical therapies. Indeed, conventional dental restorative procedures exploit therapeutic tooth ECM cross-linking to bond dental materials to sound tooth structure (Maravic et al 2021). Accordingly, when the processes involved in producing an ordered cross-linked matrix go awry, development and homeostasis are impaired.…”
Section: Ecm Scaffold: Migration and Mineralizationmentioning
confidence: 99%